Catherine, Called Birdy - Cushman, Karen; Nang Chan Yeema (New York, USA HarperTrophy Publisher, 1995)
Catherine feels trapped. Her father is determined to marry her off to a rich man-any rich man, no matter how awful.
Keywords: Adult Fiction